Frequency and Susceptibility Profile of Pathogens Causing Urinary Tract Infections in Pediatric Population - Mir, Nazia; Khurshid, Rabia; Zafar, Aizza; Saleem, Sidrah; Ch , Saadia; Ali, Uzma (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary tract infection is one of the most common cause of bacterial infection in childhood. Urinary Tract Infections are more common in pediatric population and is a major reason behind morbidity and mortality in children. Aim: To isolate most common pathogens causing UTI, their frequency and susceptibility pattern in pediatric population. Methodology: Urine samples were collected from various children with symptomatic UTI and cultured on Cysteine lactose electrolyte deficientgar. Identification of organisms was done by using microbiological techniques which included biochemical tests and gram staining. Antibiotic susceptibility pattern was achieved by Kirby Bauer disc diffusion method and results were interpreted according to Clinical Laboratory Standard Index guidelines 202. Results: Total 1200 samples were processed. Out of these samples, 492(41%) had positive bacterial growth and 59% had negative growth. Common pathogens isolated were Escherichia coli 209(42.5%), Klebsiella spp 144(29.3%), Pseudomonas spp 47 (9.6%), Enterococcus faecalis 38 (7.7%), Acinetobacter spp 37(7.5%), and Proteus spp 17 (3.5%). Overall these uropathogens exhibited better susceptibility for Colistin (84.8%), followed by Nitrofurantoin (64.7%), Amikacin (64%), Pipedemic acid 25.4%), Ceftazidime (21.4%), Nalidixic acid (18.7%), Augmentin (16.8%) and Meropenem (54%). Conclusion: This study reported a high rate of UTIs (41%) among children. A high proportion of antibiotic resistant is due to overuse of antibiotics. Incidence of UTIs can be decreased with prompt diagnosis at the right time and empirical antibiotic therapy.